Influence of CuO nanoparticles and oil concentration on the thermodynamic properties of R600a during forced boiling convection - Fernando Toapanta-Ramos; César Nieto-Londoño (International Journal of Thermofluids)
The effects of copper oxide (CuO) nanoparticles and Polyalphaolefin (PAO) lubricating oil on the thermophysical transport parameters of R600a (isobutane) and its flow boiling heat transfer coefficient are evaluated in this work using semi-empirical correlations. Commonly occurring refrigerant–oil mixes in vapor compression refrigeration cycles result from lubrication needs in system components, affecting both transport qualities and heat transfer performance. Considering the effect produced by the heat flows, 10 kW/m2, 15 kW/m2 and 20 kW/m2, to which the fluids are being subjected. This work investigates refrigerant combinations with a maximum nanoparticle–oil ratio of 5% resulting in three formulations: R600a/CuO, R600a/PAO, and R600a/CuO/PAO as modest nanoparticle concentrations can improve these qualities. Key thermal transport parameters, including density, thermal conductivity, dynamic viscosity, and specific heat, show improvement by CuO nanoparticles with oil. Still, the R600a/CuO/PAO mixture shows hardly any variation from pure R600a. The Gungor and Winterton correlation assessed the forced flow boiling heat transfer coefficient. The results reveal that whilst PAO oil reduces the coefficient at 5%, the coefficient rises with increasing concentrations of nanoparticles in the refrigerant. The heat transfer coefficient decreases slightly when both CuO and PAO are present.